Naproxcinod shows significant advantages over naproxen in the mdx model of Duchenne Muscular Dystrophy - Miglietta, Daniela (Orphanet J Rare Dis, 2015)
BACKGROUND: In dystrophin-deficient muscles of Duchenne Muscular Dystrophy (DMD) patients and the mdx mouse model, nitric oxide (NO) signalling is impaired. Previous studies have shown that NO-donating drugs are beneficial in dystrophic mouse models. Recently, a long-term treatment (9 months) of mdx mice with naproxcinod, an NO-donating naproxen, has shown a significant improvement of the dystrophic phenotype with beneficial effects present throughout the disease progression. It remains however to be clearly dissected out which specific effects are due to the NO component compared with the anti-inflammatory activity associated with naproxen. Understanding the contribution of NO vs the anti-inflammatory effect is important, in view of the potential therapeutic perspective, and this is the final aim of this study. METHODS: Five-week-old mdx mice received either naproxcinod (30 mg/kg) or the equimolar dose of naproxen (20 mg/kg) in the diet for 6 months. Control mdx mice were used as reference. Treatments (or vehicle for control groups) were administered daily in the diet. For the first 3 months the study was performed in sedentary animals, then all mice were subjected to exercise until the sixth month. Skeletal muscle force was assessed by measuring whole body tension in sedentary animals as well as in exercised mice and resistance to fatigue was measured after 3 months of running exercise. At the end of 6 months of treatment, animals were sacrificed for histological analysis and measurement of naproxen levels in blood and skeletal muscle. RESULTS: Naproxcinod significantly ameliorated skeletal muscle force and resistance to fatigue in sedentary as well as in exercised mice, reduced inflammatory infiltrates and fibrosis deposition in both cardiac and diaphragm muscles. Conversely, the equimolar dose of naproxen showed no effects on fibrosis and improved muscle function only in sedentary mice, while the beneficial effects in exercised mice were lost demonstrating a limited and short-term effect. CONCLUSION: In conclusion, this study shows that NO donation may have an important role, in addition to anti-inflammatory activity, in slowing down the progression of the disease in the mdx mouse model therefore positioning naproxcinod as a promising candidate for treatment of DMD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13023-015-0311-0) contains supplementary material, which is available to authorized users.